A Collaborative Approach to the Development of Multi-Disciplinary Teams and Services for Child and Adolescent Mental Health in Uganda - Rukundo, Godfrey Zari; Nalugya, Joyce; Otim, Patrick; Hall, Alyson (Frontiers in Psychiatry, 2020)
Background: Children and adolescents are especially vulnerable to mental, neurological and substance use disorders during various stages of their growth and development. They often require specialized personnel whose training is time consuming and costly. Consequently many children and adolescents remain untreated in developing countries. This paper describes steps Uganda is taking to develop local capacity for child and adolescent mental health services through training of multi-disciplinary teams. Methods: A 2 year training programme was introduced in accordance with the Ugandan Ministry of Health Child and Adolescent Mental Health Strategy. This had been jointly developed in 2008 by Mbarara University of Science and Technology, Makerere University, the Uganda Ministry of Health and East London Foundation NHS Trust, United Kingdom (UK). The initial funding for the programme focused on monitoring and evaluation of the training, quality of clinical practice and clinical activity data. Results: Fifty health workers have been trained and are now working at regional referral hospitals and non-governmental organizations. Monitoring and evaluation demonstrated major increases in the range of disorders and client numbers (2,184–31,034) over 6 years. There was increased confidence, knowledge and skills in assessment. Learning in a multidisciplinary environment was interesting and helpful. Assessments were more thorough and child centred and more psychological treatments were being used. Programme graduates are now contributing as trainers. Conclusion: The clinically focused multidisciplinary training has yielded rewarding outcomes across Uganda. Ongoing support and collaborative work can expand service capacity in child and adolescent mental health for Uganda and other developing countries.